PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NUSA NIPA - Laurensiana Ngguwa Modhe; Yosefina Andia Dekrita; Kristiana Reinaldis Aek (Universitas Nusa Nipa Maumere, 2026)
This study aimed to: (1) describe the financial literacy, lifestyle, and financial behaviour of students in the Management Study Program at the Faculty of Economics and Business, Nusa Nipa University; and (2) analyse the partial and simultaneous influences of financial literacy and lifestyle on financial behaviour. Descriptive analysis results indicate that financial literacy falls into the